Neonatal sepsis and its associated factors among neonates admitted to the neonatal intensive care unit in Wachemo University Comprehensive Specialized Hospital, Southern Ethiopia, 2022 - Mezgebu, Taye; Ossabo, Getachew; Zekiwos, Asnakech; Mohammed, Hamdino; Demisse, Zerihun (Frontiers in Pediatrics, 2023)
Abstract Background: Neonatal sepsis is a major public health problem worldwide. It is one of the leading causes of neonatal mortality and morbidity worldwide. Neonatal mortality is higher in developing countries, where the extent and causes of neonatal sepsis are not yet known. Neonatal sepsis is a leading cause of neonatal mortality in Ethiopia. As a result, this study aimed to assess the proportion and identify maternal and neonatal risk factors for neonatal sepsis among neonates admitted to the neonatal intensive care unit. Methods: An institutional-based cross-sectional study was conducted from May to July 2022 at the Wachemo University Comprehensive Specialized Teaching Hospital, Neonatal Intensive Care Unit, Southern Ethiopia. A total of 205 neonates with index mothers participated in the study. A structured, pretested questionnaire was used to collect data from study subjects using a consecutive sampling technique. Data was entered into Epi-Data Manager version 3.1 for Windows and then exported to SPSS version 22 for further data cleaning and analysis. Descriptive analyses were performed using frequency, percentage, and summary statistics to describe key variables. A multivariate regression model was used to identify factors associated with neonatal sepsis. Finally, statistical significance was declared at a p-value of less than 0.05, and an adjusted odds ratio with a 95% confidence level was used to declare the variable's association with the outcome variable. Result: The overall prevalence of neonatal sepsis was 39.5% (95% CI: 33.7–45.9). Taking a variable statistically significant in bivariate logistic regression as a candidate variable, multivariable analysis was performed. The multivariable model analysis found that unmarried status AOR = 18.37 (95% CI, 1.56-216.14), maternal fever during delivery AOR = 4.74 (95% CI, 1.63-13.8), and protracted rupture of membrane AOR = 7.53 (95% CI, 2.19-25.6) were variables that increased neonatal sepsis. Conclusion: The study’s findings indicate that neonatal sepsis is highly prevalent. Unmarried maternal status, maternal fever during delivery, and premature rupture of the membrane were predictors of neonatal sepsis. Therefore, it is recommended that providing training for health workers and close monitoring and evaluation during obstetric and neonatal care are crucial to halting the occurrence of neonatal sepsis.